Evaluation of strain and structural style variations along the strike of the Fuegian thrust-fold belt front, Argentina - Torres Carbonell, Pablo Juan (2013)
The Fuegian thrust-fold belt (TFB) forms the thin-skinned outer wedge of the Andes in Tierra del Fuego. Using subsurface and outcrop data from two areas (Western and Eastern) of the TFB front in Argentina we aimed to verify and characterize the apparent structural variations along the strike. Both areas reveal pro- and retro-vergent faultrelated folds detached at similar horizons, with a youngest early to middle (?) Miocene deformation age. However, the Western Area has gentle, large-wavelength folds whereas the Eastern Area is characterized by a very tight structural geometry, with closer fold geometries. This difference manifests itself in the shortening of analogous structures: below 5.5% in the west as against ~22% in the Eastern Area. Our findings verify structural style variations along the strike and suggest that the Eastern Area endured higher strain. We evaluate two possible causes of this strain gradient, assuming homogeneous regional shortening: (i) lateral rheological variations at the base of the thrust wedge, namely the occurrence of more competent beds which would have restrained the propagation of the detachment toward the east; and (ii) the effect of strong buttressing in the eastern TFB exerted by the Río Chico arch basement promontory during deformation. Published results, together with our current subsurface and outcrop data, rule out significant rheological gradients in a preferred direction along the TFB. On the other hand, we present evidence of the nucleation of frontal thrusts above basement steps at the Río Chico arch western margin, which comprise local buttresses. We speculate that this buttressing was mantained along the TFB front and is enhanced toward the east, where forward TFB propagation was hindered due to the southern projection of the Río Chico promontory. This would explain the higher strain and more complex structural style in the Eastern Area